Soil Quality (SQ) Sebagai Instrumen Monitoring dan Pengelolaan Lahan Pertanian Berkelanjutan. - Hanudin, Eko (2010)
Soil as an important land components is not renewable resouces and very vital that require a soil quality preservation technology. Sustainable agricultural systems will never be achieved when there is no serious effort and technological capabilities in managing soil quality. Intensive use of land for the production process if not properly monitored and managed, it will cause degradation of soil quality. Soil quality (SQ) implies two meanings of soil productivity and environmental capabilities. Soil quality is measured based on the observation of dynamic conditions of soil quality indicators selected from properties that show the capacity of soil functions. The selection of land quality indicators should reflect the capacity of soil to perform its functions, namely: (1). Preserve the activity, diversity and biological productivity, (2). Organize and direct the water flow and soluble substance, (3). Filtering, support, break down, detoxify inorganic materials and organic, including industrial and household waste and a precipitation from the atmosphere, (4). Store and recycle nutrients and other elements in the biosphere, and (5). Supporting economic and social structures to protect archaeological relics associated with human settlements. Thus the preparation of the soil quality index becomes very important because it can be used as an instrument to monitor critical indicators of soil quality and subsequently can be used as a basis for applying soil technology management.